2020
DOI: 10.1097/prs.0000000000006327
|View full text |Cite
|
Sign up to set email alerts
|

DaxibotulinumtoxinA for Injection for the Treatment of Glabellar Lines: Results from Each of Two Multicenter, Randomized, Double-Blind, Placebo-Controlled, Phase 3 Studies (SAKURA 1 and SAKURA 2)

Abstract: Background: DaxibotulinumtoxinA for Injection (DAXI) is a novel botulinum toxin type A formulation in clinical development. A phase 2 dose-ranging study identified an optimal dose and demonstrated efficacy with a median duration of 24 weeks. Methods: In two phase 3, multicenter, randomized, double-blind, placebo-controlled studies (SAKURA 1 and SAKURA 2), subjects with moderate or severe glabellar lines at maximum frown were assigned randomly to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…Study participants were either rollover subjects who had completed the SAKURA 1 or 2 Phase 3 studies 2 or newly enrolled (de novo) subjects. Eligible subjects included those aged 18 years or older, in good health, with moderate or severe glabellar lines based on the Investigator Global Assessment–Frown Wrinkle Severity (IGA-FWS) and Patient FWS (PFWS) scales.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study participants were either rollover subjects who had completed the SAKURA 1 or 2 Phase 3 studies 2 or newly enrolled (de novo) subjects. Eligible subjects included those aged 18 years or older, in good health, with moderate or severe glabellar lines based on the Investigator Global Assessment–Frown Wrinkle Severity (IGA-FWS) and Patient FWS (PFWS) scales.…”
Section: Methodsmentioning
confidence: 99%
“…The high level of efficacy seen with DAXI in the Phase 2 glabellar lines study was confirmed with consistent results demonstrated in the SAKURA 1 and 2 trials involving a combined total of 609 subjects (405 subjects received a single treatment of DAXI 40U and 204 subjects received placebo). 2 The primary efficacy end point was achieved in both the SAKURA 1 and 2 trials, and the median duration of none or mild glabellar line severity was 24.0 weeks. In the Phase 2, dose-ranging and both Phase 3 SAKURA trials, the adverse event (AE) profile was similar to that seen with other neuromodulators, and no new safety signals were identified.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Botulinum toxin type A (BTX-A), also known as onabotulinumtoxinA or Botox R , is widely known for its cosmetic efficacy in treating glabellar frown lines (8). It was estimated that more than 1 million cases of BTX-A treatment were reported annually in the United States (9).…”
Section: Introductionmentioning
confidence: 99%